BANGTANBOYS (BTS) MEAL DARI PERSPEKTIF MASYARAKAT KONSUMSI PADA KOMUNITAS ARMY INDONESIA AMINO (BAIA) BALI - Lakamola, Vivin Christin Mutiara; Punia, I Nengah; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Boyangroup Bangtan Sonyeondan (BTS) is one of the most popular and influential music groups in the world today. BTS has a very large and loyal fan base, known as ARMY and spread all over the world. This situation made the McDonald's franchise company choose BTS for collaboration by presenting a menu called the BTS Meal which became very popular and was attacked by many people when it was launched. The research focus uses the theory of consumption society from Jean Baudrillard. The consumption community selected in this study focuses on the BTS ARMY Indonesia Amino (BAIA) Bali community which was established in 2017 which buys BTS Meal. Researchers analyzed the perspectives of BAIA Bali members in interpreting BTS Meal as a commodity that is consumed using a qualitative approach with a descriptiveexplanative research type. The results of the study show that there are different perspectives from the original purpose of creating the BTS Meal menu due to the sign values that are interpreted and created by the individuals themselves in interpreting the BTS Meal. Simulacra and hyperreality direct people to consume for momentary interests, satisfy desires and also form self-image. The symbolic value in the BTS Meal menu is not just a food package that is consumed for primary needs (use value) but has turned into a food package menu that is consumed for the purpose of filling an apparent need in order to fulfill one's own prestige (sign value). The implications of BTS Meal for consumption society can be seen in the increasing interest and demand, tending to follow trends and wanting to try things that are currently popular, as well as close experiences with their idols through food products. Keywords: BTS Meal, ARMY, BAIA Bali, Consumer society, Sign value & Use value